2011
DOI: 10.1021/je101178u
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Viscosity−Density Measurements on Ethane and Propane over a Wide Range of Temperature and Pressure Including the Near-Critical Region

Abstract: An apparatus combining a vibrating-wire viscometer and a single-sinker densimeter was used to provide accurate ηρpT data for four isotherms on ethane at (293.15, 307.15 [ethane 3.5 and 5.0], and 423.15) K and five isotherms on propane at (273.15, 298.15, 366.15, 373.15, and 423.15) K. The maximum pressure was chosen to be about 95 % of the saturated vapor pressure for the subcritical isotherms and 30 MPa at maximum for the supercritical isotherms. The relative uncertainty in the density is estimated to be less… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 38 publications
0
26
0
Order By: Relevance
“…5, the viscosity values obtained using the adjusted potential function, η adj , are compared with those obtained using the unadjusted one, η unadj , with the experimental data reported by Seibt et al, 60 sets are the most accurate to date for propane in the dilute gas phase with an uncertainty of only 0.3%. They are mutually consistent and extend over the whole range of temperatures at which experimental data for the gas phase are available (273 K to 625 K).…”
Section: B Resultsmentioning
confidence: 99%
“…5, the viscosity values obtained using the adjusted potential function, η adj , are compared with those obtained using the unadjusted one, η unadj , with the experimental data reported by Seibt et al, 60 sets are the most accurate to date for propane in the dilute gas phase with an uncertainty of only 0.3%. They are mutually consistent and extend over the whole range of temperatures at which experimental data for the gas phase are available (273 K to 625 K).…”
Section: B Resultsmentioning
confidence: 99%
“…In principle, the impact of the uncertainties of Δ T and Δ p is minor in wide thermodynamic regions due to its small values, as proven by Seibt et al for the measurements on helium and nitrogen, for which the total uncertainty of the density determination was true(Δρ/ρtrue)tot0.1% for ρ>15 kg normalm3. But near the critical region, a significant influence on the uncertainty of the density follows from the distinctly increased values for the partial derivatives ( ∂ρ∕∂T ) p and ( ∂ρ∕∂p ) T , as illustrated by Seibt et al for ethane and propane.…”
Section: Methodsmentioning
confidence: 95%
“…Seibt et al demonstrated the performance of the combined viscometer‐densimeter on the basis of measurements on helium and nitrogen. In addition, they carried out a profound error analysis, which was extended to the somewhat more challenging situation of measurements on fluids like ethane and propane, particularly with regard to the near‐critical region …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…and of Seibt et al24 are situated, an expanded uncertainty of 1.5% is assumed. In the near-critical region 1.001 < T /T c < 1.010 and 0.8 < ρ/ρ c < 1.2, the expanded uncertainty is estimated to be 3.0%, increasing with decreasing temperature.…”
mentioning
confidence: 99%